THE EFFECT OF USING FINANCIAL DERIVATIVES ON SYSTEMATIC RISK IN THE GCC MARKETS - Jibai, Hussein (2015)
The echo of Financial Derivatives has reached almost all over the financial world. These instruments are financial backbones and daily routines in some markets, whereas in other markets they are still being newly introduced and explained. With the business world growing and developing nowadays, the theoretical and technical understanding of risk is magnificently demanded and it has consequently been given much attention as academia had dedicated certificates and different masters’ degrees that tackle risk and its mitigation. On one hand, derivatives can be used for hedging purposes. On the other hand, they can be used for speculation. This paper studies the effect of using financial derivatives by non-financial firms listed in the Gulf Cooperation Council stock exchanges on systematic risk measured by beta (β). After taking a sample of 348 non-financial firms, the study finds out that the use of derivatives, in general, in this Middle Eastern area, significantly decreases the systematic risk faced by the users. Moreover, the study finds out that the most frequently used type of derivatives in the area, interest rate derivatives, also significantly decreases beta. The study involves panel data and covers the time span between 2013 and 2014. The results of this paper are fruitful and agree with the global finance literature that describes the ability of financial derivatives to reduce systematic risk.